Teneurins and Teneurin C-Terminal Associated Peptide (TCAP) in Metabolism: What’s Known in Fish? - Reid, Ross M.; Freij, Khalid W.; Maples, Joel C.; Biga, Peggy R. (Frontiers in Neuroscience, 2019)
Teneurins have well established roles in function and maintenance of the central nervous systems of vertebrates. In addition, teneurin c-terminal associated peptide (TCAP), a bioactive peptide found on of the c-terminal portion of teneurins, has been shown to regulate glucose metabolism. Although, the majority of research conducted on the actions of teneurins and TCAPs has strictly focused on neurological systems in rodents, TCAP was first identified in rainbow trout after screening trout hypothalamic cDNA. This suggests a conserved functional role of TCAP across vertebrates, however the current depth of literature on teneurins and TCAPs in fish is limited. In addition, the overall function of TCAP in regulating metabolism is unclear. This review will highlight work that has been conducted specifically in fish species in relation to the teneurin system and metabolism in order to identify areas of research that are needed for future work.